Comparison of various decalcificators in preparation of DNA from human rib bones - Żołędziewska, Magdalena; Gronkiewicz, Stanisław; Dobosz, Tadeusz (Anthropological Review, 2002)
Various calcium-binding buffers and agents in DNA preparation from fresh human rib bones were compared. We showed that the buffer described by Kuntze et al. [1996] yielded the highest quantities of DNA, but the obtained DNA was strongly degraded. The best quality DNA was obtained using two buffers: of Hänni et al. [1994] and of Ivanov et al. [1995]. Among the new calcium-binding agents that were not examined before, the most efficient were Bismuth III Oxide and Na/FeEDTA, and – in two-step decalcification – sodium citrate.